UPAYA GURU MENINGKATKAN MEDIA BELAJAR BERBASIS TEKNOLOGI - Chronika Febrianti; Delta Fariza; Fepriana Asiska; Fely Eclasya; Palija Lubis; Sondang Kiki Febrianti Pane; Jamaludin Jamaludin (CV. ADIBA AISHA AMIRA, 2023)
An effective and efficient learning process requires a fixed learning strategy where a teacher must also carry out or design good learning so that it is able to achieve the right goals. where this study aims to improve the ability of teachers to use information and communication technology (ICT) in the learning process. information (IT) as a learning medium in this first cycle, however, the implementation of the use of information technology has increased, as evidenced by the level of developmental achievement. Starting with this training activity there will be an increase in the ability of a teacher in terms of managing technology-based learning where this ability is in the pedagogic competence.